Keanekaragaman gastropoda di perairan Teluk Lembar, Nusa Tenggara Barat - Hafish, Nyutriawan Arkan; Kurniawan, Rahmat; Probosunu, Namastra; Adharini, Ratih Ida; Setyobudi, Eko (Jurnal Biologi Udayana; Vol 26 No 1 (2022): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2022.v26.i01.p05, 2022)
Research on gastropod diversity has been carried out in Lembar Bay, which is located in the southwest of Lombok Island, West Nusa Tenggara. This area has a unique environment, characterized by mangrove forests, domestic activities, and traffic of marine transportation. This research aimed to know the diversity of gastropods in this location. The research was conducted from July to August 2017. The sample of gastropod was collected using Ekman grab with size 12.5 x 20 cm from 11 stations based on the environmental condition. Water quality consists of temperature, substrate, depth, water pH, salinity, and organic matter was measured following the location of the sampling station. The gastropod data obtained were analyzed to determine the index of density, diversity, and dominance. The identified gastropod species from Lembar Bay were grouped into 31 genera and 21 families. Clypeomorus purpurastoma , Pirenella asiatica , and Terebralia palustris were the common species found in Lembar Bay, with 16.76%, 13.8% and 12.6%, respectively. The density index was 2.675 ind/m 2 . Gastropods community showed a moderate level of diversity (H’=1.23) with a low level of dominance (D= 0.09).